Estimating the potential of electric mobility in commercial transport considering the availability of charging infrastructure – A behavioural model analysis for the city of Hamburg. (June 2022) - Rosenberger, Kerstin; Tapia, Rodrigo; Friedrich, Hanno; Flämig, Heike
Abstract: To address climate change, transport policy tries to accelerate the electrification of vehicles. The impact of policy measures taken is difficult to predict especially in areas like commercial passenger transport where few research exists. In this study we estimate the impact of higher availability of charging infrastructure on the electrification potential of vehicles used in commercial passenger transport. For Hamburg we estimate that the electrification potential could increase by about 35%. We base this analysis on a company survey on vehicle usage patterns in commercial passenger transport and a ranked choice model to quantify the relationship between company sectors and tour patterns. This enables us to estimate the impact on electrification potential for overall Hamburg. The methodological contribution of this paper is to demonstrate a statistically viable approach to extrapolate insights from a behavioural survey to an overall region in the context of commercial passenger transport.